Objective assessment of surgical technique in rotation and nasal projection variation - Fagundes,Marina Serrato Coelho (2016)
ABSTRACT INTRODUCTION: In rhinoplasty, facial esthetic analysis is critical for proper surgical planning. Parameters such as rotation and nasal projection should be routinely evaluated. Few studies have objectively assessed changes in facial angles postoperatively. OBJECTIVE: To evaluate the effectiveness of medial intercrural sutures and of rotation of the nasal tip on the increase of rotation and nasal projection in Caucasian patients undergoing primary rhinoplasty. METHODS: A prospective study carried out between 2011 and 2013, with 27 patients treated with primary rhinoplasty with a basic technique by the same surgeon, with medial intercrural sutures and rotation of the nasal tip. Rotation and nasal projection were measured from photographs obtained preoperatively and after 12 months. RESULTS: All 27 patients completed the study. The mean age was 27.1 years. There was a mean increase of 8.4° in the rotation - a statistically significant value. There was no significant change in the projection. CONCLUSION: The medial intercrural and nasal tip rotation sutures are effective in increasing nasal rotation in Caucasian patients undergoing rhinoplasty.